KUALITAS PELAYANAN ADMINISTRASI BERDASARKAN PELAKSANAAN SISTEM INFORMASI MANAJEMEN RUMAH SAKIT (SIMRS) PADA PELAYANAN PASIEN DI RSUD Dr. MM DUNDA LIMBOTO KABUPATEN GORONTALO - Kurniati Mohi, Widya; Sahi, Nirmala; Akuba Mootalu, Fatma (STISIPOL Mujahidin Buol, 2022)
This research aims to determine how the Implementation of Management Information System Policy (SIM RS) at RSUD Dr. MM Dunda Limboto. This research uses a qualitative approach with descriptive type. Data collection techniques are using observation sheets or direct interviews with informants. The results of this study are 1). Patient data collection often experiences problems with internet services with limited capacity, so patient data is always late. 2) The quality of the internet network is often an obstacle for SIMRS administrative officers who are not only accepting patients in general, but must pay attention to the quality of service in the form of increasing internet network capacity. So it can be concluded that the quality of administrative services based on the implementation of the hospital management information system (SIMRS) in patient care at RSUD. Dr. MM Dunda Limboto, Gorontalo Regency cannot be said to have run optimally because it still has obstacles, especially regarding facilities and infrastructure such as the internet network which is still slow and takes a long time.